Ethics of Election Organizers in the Implementation of Simultaneous Regional Elections in 2024 - Dewi, Lia Riesta; Novita, Maya Sri (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2025)
This study focuses on looking at the dynamics and constellation of the ethics of the Election Commissions in organizing the 2024 Simultaneous Regional Elections. This paper aims to gain an understanding of two things. First, the implementation of ethics institutionalization and enforcement of election ethics. Second, the dynamics of the development of the ethics of election organizers in the implementation of the 2024 simultaneous regional elections. The paper is prepared based on normative legal research based on secondary data. The results of the study found that: first, the ethics of the Election Organizer are enforced with a tiered source of national ethics starting from Pancasila as philosofische grondslag to DKPP Regulations related to the Election Organizer's Code of Ethics. Second, the integrity and professionalism of the election can be realized if the Election Organizer in interpreting the code of ethics is guided by the principles of the Election Organizer's code of ethics.